Public Debt, Inequality and Power. The Making of a Modern Debt State - Sandy Brian Hager (University of California Press, 2016)
Who are the dominant owners of US public debt? Is it widely held, or concentrated in the hands of a few? Does ownership of public debt give these bondholders power over our government? What do we make of the fact that foreign-owned debt has ballooned to nearly 50 percent today? Until now, we have not had any satisfactory answers to these questions. Public Debt, Inequality, and Power is the first comprehensive historical analysis of public debt ownership in the United States. It reveals that ownership of federal bonds has been increasingly concentrated in the hands of the 1 percent over the past three decades. Based on extensive and original research, Public Debt, Inequality, and Power will shock and enlighten. “These days, the topic of America's debt stirs heated political debate. But one of the most important facts in this discussion has hitherto been obscured: who actually owns that debt inside America? Hager has done some fascinating and pathbreaking research to answer that question and concluded that the ownership pattern is surprisingly concentrated—and unequal—and that this may have implications for how the entire debt debate develops in the coming years. This is an illuminating work that deserves wide attention.” (GILLIAN TETT, Financial Times) “The relationship between the ownership structure of government debt and economic inequality—between public finance and the class structure of modern capitalism—is one of several central concerns of political economy that has been almost completely neglected in recent decades. Sandy Brian Hager's book returns to the subject with theoretical and empirical bravado.” (WOLFGANG STREECK, Director Emeritus, Max Planck Institute for the Study of Societies) “Money is power, and US Treasury debt is the world's single largest financial instrument. Hager's insightful book fills an enormous hole in our knowledge of who owns this debt and how the power flowing from that increasingly concentrated ownership affects US and global politics.” (HERMAN M. SCHWARTZ, author of Subprime Nation: American Power, Global Capital, and the Housing Bubble) *** SANDY BRIAN HAGER is Postdoctoral Fellow at the Weatherhead Center for International Affairs at Harvard University. He has published in various journals, including New Political Economy and Socio-Economic Review. [This book is distributed under the terms of the Creative Commons Attribution + Noncommercial + NoDerivatives 3.0 license. Copyright is retained by the author(s)]
Keywords: 330; capital; distribution; economic policy; interest; ownership; power; public debt; spending; state; subsidies; tax; United States